1979
DOI: 10.1029/jb084ib14p08404
|View full text |Cite
|
Sign up to set email alerts
|

Mars: CO2 adsorption and capillary condensation on clays—significance for volatile storage and atmospheric history

Abstract: We report results on the adsorbate-adsorbent system CO2-nontronite at 230øK, 196øK, and 158øK, covering the range of subsurface regolith temperature on Mars. These results, together with Viking observations have allowed construction of a three-part regolith-atmosphere-cap model describing storage and exchange of atmosphere-exchangeable CO2. Cold nontronite, and 'expanding' clays in general, are far better adsorbers for CO2 than cold pulverized basalt and exhibit far more complex adsorptive properties as well. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 37 publications
(36 reference statements)
0
37
0
Order By: Relevance
“…A previously unidentified deposit of solid CO 2 was discovered by the Mars Reconnaissance Orbiter, in the form of bodies of CO 2 ice embedded within the martian south polar layered deposits (Phillips et al 2011) with an amount equivalent to a global pure CO 2 atmospheric pressure of 4-5 mbar. More substantial amounts of CO 2 could be adsorbed in the regolith, up to ≈140 mbar (Fanale and Cannon 1979). CO 2 may also be present in the martian cryosphere in the form of CO 2 clathrate hydrates (Mousis et al, this issue), although in unknown amounts.…”
Section: Co 2 Budget Of Marsmentioning
confidence: 99%
“…A previously unidentified deposit of solid CO 2 was discovered by the Mars Reconnaissance Orbiter, in the form of bodies of CO 2 ice embedded within the martian south polar layered deposits (Phillips et al 2011) with an amount equivalent to a global pure CO 2 atmospheric pressure of 4-5 mbar. More substantial amounts of CO 2 could be adsorbed in the regolith, up to ≈140 mbar (Fanale and Cannon 1979). CO 2 may also be present in the martian cryosphere in the form of CO 2 clathrate hydrates (Mousis et al, this issue), although in unknown amounts.…”
Section: Co 2 Budget Of Marsmentioning
confidence: 99%
“…Conversely, at minimum obliquity, polar temperatures would be 15 ° lower than at present and equatorial temperatures slightly warmer (Ward, 1974). Fanale and Cannon (1979) showed that for their nontronite model, these temperature fluctuations result in an atmospheric pressure that varies between 0.5 and 22 mb. A regolith of fine-grained basalt would result in smaller variations.…”
Section: Near-surface Storage Of Carbon Dioxidementioning
confidence: 99%
“…It is reasonable, therefore, to conclude that these eroded debris blankets at mid to high latitudes are similar to the materials analyzed at the Viking sites; that is, they consist largely of weathered debris and may contain a significant fraction of montmorillonitic clays (Toulmin et al, 1977). Fanale and Cannon (1979) showed that montmorillonite clays have a substantial adsorptive capacity for CO2 and that the capacity depends sensitively on temperature. For example, under a 6.1-mb CO2 atmosphere, nontronite, an Fe-rich montmorillonite, can adsorb 11 cm a (STP) COz/g at 158°Kbut only 3.5 cm 3 at 196°K.…”
Section: Near-surface Storage Of Carbon Dioxidementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the available observations point to the conclusion that the total mass of permanent, solid CO2 at the south residual cap is not sufficient to control the mass of the Martian atmosphere over climatic time scales. Fanale and Cannon [1979] have estimated that if the cap was uniformly covered with a 400-m-thick layer of CO2 frost, it could contain at most the equivalent of I present Martian atmospheric mass of solid CO2. If a residual water ice cap was exposed in 1969 [Jakosky and Barker, 1984] We now present the IRIS and imaging data sets and describe our data reduction and analysis procedures.…”
Section: Introductionmentioning
confidence: 99%